Métodos nutricionais de muda forçada em poedeiras semi-pesadas. - Girardon, Juliana Cardoso (2011)
This study aimed to investigate four forced-moulting methods on productive performance and egg quality of brown-egg layers. A total of 448 100 week-old laying hens were fed experimental diets during 148 days (from August to December of 2009). The experimental design was a completely randomized block design, with 16 replicates per treatment. Treatments consisted of: 1) fasting during 14 days; 2) soybean hulls based diet; 3) wheat bran based diet and 4) High tannin sorghum based diet. A post-moulting corn-soybean meal basal diet, formulated to fulfill nutrient requirement of birds was fed to the animals. Hens fed alternative ingredient based diets showed better performance. Productive performance, viability and decrease in egg production were similar between hens fed the soybean hulls based diet and those exposed to fasting. Birds fed high tannin showed lower mortality, but showed a lower egg production. Birds fed alternative ingredients showed 12% egg production at 6 days after the beginning of the experiment. These results indicate that hens fed alternative ingredient sources showed better performance than those exposed to fasting at the end of the first productive cycle.